Mengevaluasi Perkembangan Study Al Quran di Nusantara Dalam Kurun Waktu Tahun 1960-2000 M - Laila, Itsna Noor (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This article discusses the development of the study of the Qur’an (interpretation of the Qur’an) in the archipelago from 1960 AD to 2000 AD. This article also analyzes various forms and styles of interpretation, as well as the teaching of interpretation that developed in that period. In its research, this article employs qualitative methods, specifically library research. As a reference source, this article utilizes books on the history of interpretation development as primary sources, along with other relevant books, articles, and literature on the topic of discussion as secondary sources. To collect research data, researchers used documentation techniques by collecting several references and books related to the research theme. This data was then analyzed using descriptive analysis techniques with a historical approach to examine the genealogy of the development of interpretation in the archipelago from 1960 to 2000.